Strengthening the Competencies of Target Teacher in Assistance of Curriculum 2013 Implementation in Tanggamus Regency - Lampung Province - Mohammad Masykuri (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2017)
Development stage of curriculum 2013 has entered the limited-implementation phase to secondary schools. To maintain and improve the sustainability of the understanding and implementation of curriculum 2013, the government has programmed assistance activities for teachers and principals. This programs conducted as reinforcement in understanding the concept of Curriculum 2013 and to help overcome the obstacles that arise during the curriculum implementation. The research objective is to obtain information on the assistance of Curriculum 2013 implementation in accordance with the philosophy, concepts, rules, principles, meaning and procedures included in the elements of the curriculum changes based on Graduate Competence Standard (GCS), Core Competencies (CC) and Standard Competencies (SC) in Tanggamus regency, province of Lampung. The result of the research showed that there are the strengthening competency of target teacher during the mentoring conducted by the core/assistant teacher. The strengthening competencies includes the understanding of: 1) textbooks and teachers' manuals, 2) learning and assessment process, 3) the preparation of lesson plan, 4) learning implementation.